The level of knowledge of paramedics from Podkarpackie Province about the use of simulation in training - Szela, Stanisław; Surowiec, Tomasz; Ozga, Dorota; Kiszka, Jerzy; Jędrzejczyk–Cwanek, Marzena (Journal of Education, Health and Sport, 2017)
Introduction: Medical Simulation allows to improve knowledge, skills and social competences in undergraduate and post-graduate training in medical professions in a shorter time than traditional education. The aim of the paper was to assess the level of knowledge of paramedics on the use of medical simulation during undergraduate education in the field of emergency medicine. Material and Method The study was conducted from January to June 2014 among 60 paramedics from the Podkarpackie Province aged over 21. The research tool was the questionnaire developed by the authors. Results Men dominated in the study (18% women and 82% men). The most numerous group were the youngest subjects, i.e. between 21 and 30 (76%), and the smallest group was the oldest, i.e. over 40 (7%). The study demonstrated the relationship between respondents’ responses regarding the use of patient simulators during university or postsecondary training and their self-assessment in terms of improved practical skills and their positive effect on the communication of paramedics with patients. Self-assessments of paramedics in terms of the increase of their practical skills through medical simulators correlated with the suitability of these skills in daily work and the impact on communication of medical rescue teams. Conclusions The medical simulation is used in the education of the students of medicine, but it is also of great importance in terms of modern teaching in emergency medicine, nursing, obstetrics in under and postgraduate education.